The Mieroszewski Centre – legal and financial issues - Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu)
This article is about the Mieroszewski Centre, which is a state legal entity and considered a unit of the public finance sector. The paper presents the Centre's genesis, legal status, organisation, goals and tasks. It then analyses the Centre's financial plan, income and expenditure. The article concludes with a summary and a de lege ferenda conclusion.